Structure and properties of metal nanoparticles on carbon nanostructures - Lodge, R. W. (2017)
The work presented in the thesis describes the preparation and characterisation of nanoparticle-carbon nanotube composite structures by transmission electron microscopy (TEM) and their applications in catalysis and biomedicine. Identical location TEM (IL-TEM) was utilised for the first time to study the nanoscale structure of composites of catalytic metallic nanoparticles and hollow carbon nanotubes in macroscale, liquid-phase, preparative reactions. IL-TEM analysis of palladium nanoparticles confined within graphitised nanofibres (GNF) indicated that the catalytic nanoparticles undergo changes in mean size and size-dependent migrations within the internal channel of GNF under the conditions of Suzuki-Miyaura reactions. IL-TEM analysis of copper nanoparticles in GNF showed dissolution and reprecipitation of the nanoparticles into strand-like nanostructures under the conditions of the “click” reaction, indicating the pseudo-homogeneous mechanism of this catalysed chemical transformation. A series of metal nanoparticle-GNF catalysts were subject to a range of elevated temperatures and gaseous environments and the corresponding structure-function relationships explored. A copper nanoparticle-GNF catalyst was applied in the industrially-significant water-gas shift reaction (WGSR) and compared to a commercially available, metal oxide-supported catalyst. The commercial catalyst exhibited minimal and expected changes in composition under the WGSR and generally remained stable with no changes in mean size or shape of catalytic nanoparticles. In contrast, the structure and composition of both the catalytic nanoparticles and the GNF substrate was found to significantly change in the novel nanoparticle-GNF catalyst. The effect of pre-treatment temperatures and gaseous environments on the composition and structure of three separate palladium, gold and copper nanoparticle-GNF systems was appraised, evidencing clear structure-function relationships between the size and/or composition of the catalysts at the nanoscale with their catalytic properties (selectivity and/or activity) at the macroscale. Molecule-nanotube interactions were studied towards the development of an effective controlled drug release system. The uptake and release of a chemotherapeutic agent, doxorubicin, from carbon, boron nitride and titania nanotubes, and their corresponding gold nanoparticle composites, was studied. No release of doxorubicin was observed for any structure, even with a plasmonic heating-induced release mechanism for the gold nanoparticle-nanotube composites, due to the strength of the host-guest interaction between the drug and the nanotubes.